2020
DOI: 10.1186/s43044-020-0039-6
|View full text |Cite
|
Sign up to set email alerts
|

Gender differences in clinical features and complications of infective endocarditis: 11-year experience of a single institute in Egypt

Abstract: Background: No data exists about the gender differences among patients with infective endocarditis (IE) in Egypt. The objective was to study possible gender differences in clinical profiles and outcomes of patients in the IE registry of a tertiary care center over 11 years. Results: The IE registry included 398 patients with a median age of 30 years (interquartile range, 15 years); 61.1% were males. Males were significantly older than females. Malignancy and recent culprit procedures were more common in female… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
43
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(49 citation statements)
references
References 47 publications
5
43
0
1
Order By: Relevance
“…Estrogens may play a protective role against endothelial damage. Moreover, females tend to encounter heart disease at an older age and have a higher incidence of comorbid conditions, which may result in a worse outcome [ 2 , 3 ]. Deepening the analysis, we found that the female gender was not an independent predictor of adverse prognosis, as opposed to age and EUROSCORE II, that confirmed to be independent predictors at multivariate analysis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Estrogens may play a protective role against endothelial damage. Moreover, females tend to encounter heart disease at an older age and have a higher incidence of comorbid conditions, which may result in a worse outcome [ 2 , 3 ]. Deepening the analysis, we found that the female gender was not an independent predictor of adverse prognosis, as opposed to age and EUROSCORE II, that confirmed to be independent predictors at multivariate analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Despite recent diagnostic and therapeutic advances, the mortality of IE remains high in most series, with in-hospital mortality even of 24% [ 1 ], and three-year mortality over 30% [ 2 ]. The literature reports some prognostic factors associated with higher mortality, such as advanced age, female gender [ 1 – 3 ], prosthetic valve endocarditis [ 4 ], Staphylococcus aureus aetiology [ 5 ], comorbidity [ 6 12 ], leucocytosis, hypoalbuminemia, C-reactive protein levels, elevated ERS [ 13 ], and IE complications [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, a recent systematic review of observational series from Portugal 17 concluded that a higher prevalence of men was noted in all studies and this predominance was also noted in all surgical series (men constituted more than two-thirds of all operated patients). Still, scarce and conflicting evidence persists regarding the influence of gender on the access to cardiac surgery and fatal outcome, [18][19][20][21][22][23][24] being mostly based on single-center cohorts. Populational studies addressing this issue are rare, 23 yet crucial to avoid selection bias in observational studies performed in tertiary centers.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study that explored the sex-related differences in patients with infective endocarditis has shown that women are characteristically younger, are more predisposed to cardiac lesions (rheumatic mainly), and suffer more complications than men. Alternatively, men with infective endocarditis mostly were intravenous drug abusers on a background of a structurally normal heart [35].…”
Section: Infective Endocarditis In Womenmentioning
confidence: 99%